'Las cosas se pueden hacer de modo distinto' (Aurelio Meza): understanding concepts of locality, resistance and autonomy in the cardboard publishing movement. Issue 1 (2nd January 2017) - Bell, Lucy
Abstract : Editoriales cartoneras are independent publishers who make their books out of recycled cardboard. They have spread across and beyond Latin America over the last fourteen years (since the birth of Eloísa Cartonera in Buenos Aires in 2003). They have often defined themselves, and been defined by critics, against transnational publishing corporations, but descriptions of this 'resistance' are often vague and sometimes contradictory.This is the first study to focus on the relationship between cartoneras and multinational publishers, examining areas of opposition and overlap. The paper begins by exploring the effects of the rise of transnational corporations on the world of publishing in Latin America, including neo-imperialistic centralization, concentration, and capture by market and political forces. It then turns to two case studies based (principally) in Mexico: La Verdura Cartonera and Pensaré Cartoneras . Close readings combined with interview materials illuminate the principles and practices of cartoneras, from community and collaboration to marginality and autonomy, that challenge those of transnational publishing corporations. My contention is that, while these tiny publishing projects cannot possibly 'compete' with such large corporations, what they can do is open spaces in which – to use the words of Aurelio Meza ( Kodama Cartonera ) – things can be done differently.